Therapeutic Efficacy of Stem Cells Transplantation in Diabetes: Role of Heme Oxygenase - Raffaele, Marco; Li Volti, Giovanni; Barbagallo, Ignazio A.; Vanella, Luca (Frontiers in Cell and Developmental Biology, 2016)
The growing data obtained from in vivo studies and clinical trials demonstrated the benefit of adult stem cells transplantation in diabetes; although an important limit is represented by their survival after the transplant. To this regard, recent reports suggest that genetic manipulation of stem cells prior to transplantation can lead to enhanced survival and better engraftment. The following review proposes to stimulate interest in the role of heme oxygenase-1 over-expression on transplantation of stem cells in diabetes, focusing on the clinical potential of heme oxygenase protein and activity to restore tissue damage and/or to improve the immunomodulatory properties of transplanted stem cells.